'There are Some Perversities that Cannot Stand': Nostalgia, Homosexuality, and the Continuation Novel. (March 2020) - Bernthal, J. C.
Abstract : Crime fiction scholars tend to ignore continuation novels (written as part of an established series after its creator's death) despite their importance in the international literary marketplace. As these novels exist in dialogue with their own contexts and those of their predecessors, they raise important questions about the handling of social mores. This article examines the presentation of homosexuality and its connection to criminality in two twenty-first century continuation novels, Anthony Horowitz's The House of Silk (2011) and Stella Duffy's Money in the Morgue (2018). Horowitz's deliberately conservative novel uses the Victorian context to present a relationship between male homosexuality, conspiracy, and paedophilia that would be unacceptable in a 'contemporary' mainstream crime novel. Duffy's rewriting of Ngaio Marsh's unfinished Roderick Alleyn novel, however, creates a dialogue with lesbian history in the context of speculation around Marsh's own repressed sexuality.